The Regulation and Implementation of Corporate Social Responsibility by Foreign Direct Investment in Block Pase Upstream Oil and Gas Sector, East Aceh Regency - Hidayah Balqis; Nurdin MH (Student Journal of International Law, 2022)
This research aims to explain how the regulation of CSR and what factors support and hinder the implementation of CSR in foreign direct investment in the upstream oil and gas sector in the Pase Block, East Aceh. The writing of this thesis uses a normative juridicial  method. The result of the study shows that the implementation of CSR in the Pase Block was not in accordance with UU No. 11 Tahun 2006 tentang Pemerintahan Aceh, Qanun Aceh No. 5 Tahun 2018 tentang Penanaman Modal, Qanun Kabupaten Aceh Timur No. 12 Tahun 2016 tentang TJSLP, Peraturan Gubernur No. 65 tahun 2016 tentang Pedoman Pelaksanaan TJSLP and  ISO 26000, as well as Production Sharing Contract between parties.the company has not implement CSR in accordance with the laws and regualtions due to lack of commitment of TPI to implement CSR. As a result, the CSR  has not had a positive impact on the economic growth of community and the environment around the company.